Analysis of Demand for Domestic Chicken Meat Consumption in North Sulawesi Province, Indonesia - Tumbuan, Willem JF Alfa; Jan, Arrazi Hasan; Palandeng, Indrie Debbie (Research Parks Publishing LLC, 2022)
Chicken meatis a popular food source for the people of Indonesia, even the world. This fact is accompanied by the large amount of chicken meat that has been consumed by the Indonesian people, which is 2.14 million tons and continues to increase based on a survey by the Central Statistics Agency (BPS) in 2018.The increase in demand for chicken meat products in Indonesia is not only influenced by the increase in population, but also by prices, incomes and tastes of the Indonesian people. Based on BPS data, national chicken meat production in Indonesia, between 2012 and 2020 continues to experience a significant increase, but specifically for native chicken meat products, it is still far below the increase in chicken meat production in general. This is also the case in North Sulawesi Province, which is the location of this research. This research, which was conducted in early to mid-2021, aims to analyze demand (the influence of price, income and taste variables) on the consumption of free-range chicken meat in North Sulawesi. The sample in this study were domestic chicken meat consumers in North Sulawesi Province. The results showed that partially or simultaneously the variables of demand used in this study, namely: price, income and taste have a positive effect on the consumption of native chicken meat in North Sulawesi Province.